Mutagenesis of FAD2 genes in peanut with CRISPR/Cas9 based gene editing - Mei Yuan (BMC Biotechnology, 2019)
Abstract Background Increasing the content of oleic acid in peanut seeds is one of the major goals in peanut breeding due to consumer and industry benefits, such as anti-oxidation and long shelf-life. Homeologous ahFAD2A and ahFAD2B genes encode fatty acid desaturases, which are the key enzymes for converting oleic acid to linoleic acid that oxidizes readily. To date, all high oleic acid peanut varieties result from natural mutations occurred in both genes. A method to induce mutations in the genes of other elite cultivars could speed introgression of this valuable trait. The gene-editing approach utilizing CRISPR/Cas9 technology was employed to induce de novo mutations in the ahFAD2 genes using peanut protoplasts and hairy root cultures as models. Results The hot spot of natural mutation in these genes was selected as the target region. Appropriate sgRNAs were designed and cloned into a CRISPR/Cas9 expression plasmid. As a result of CRISPR/Cas9 activity, three mutations were identified - G448A in ahFAD2A, and 441_442insA and G451T in ahFAD2B. The G448A and 441_442insA mutations are the same as those seen in existing high oleate varieties and the G451T is new mutation. Because natural mutations appear more often in the ahFAD2A gene than in the ahFAD2B gene in subspecies A. hypogaea var. hypogaea, the mutations induced in ahFAD2B by gene editing may be useful in developing high oleate lines with many genetic backgrounds after validation of oleic acid content in the transformed lines. The appearance of the G448A mutation in ahFAD2A is a further benefit for high oleic acid oil content. Conclusions Overall, these results showed that mutations were, for the first time, induced by CRISPR-based gene editing approach in peanut. This research demonstrated the potential application of gene editing for mutagenesis in peanut and suggested that CRISPR/Cas9 technology may be useful in the peanut breeding programs.